Mecanismos Fisiopatológicos do Infarto Agudo do Miocárdio: Uma Revisão Atualizada - Silva , Marcelle Cristina da (2024)
This article provides an updated review of the pathophysiological mechanisms of acute myocardial infarction (AMI) and discusses emerging therapeutic approaches. In the introduction, we highlight the importance of the topic and define the objectives and scope of the review. The methodology describes the search strategy for relevant studies, including databases used, search terms, and inclusion/exclusion criteria. The results are presented in three main topics: therapeutic strategies based on tissue engineering and cell therapy; the role of inflammation and immune response; and advances in the treatment of AMI without significant coronary obstruction (MINOCA). The discussion addresses the implications of these results, highlighting the limitations and recommending directions for future research. We conclude that, despite the challenges, innovative approaches in cardiac tissue regeneration and modulation of the inflammatory response offer new hopes for the treatment of AMI. The personalization of treatment and the integration of emerging technologies are identified as the most promising frontiers in improving care and outcomes for patients with AMI.